The Change Process from Private Company to Public Listed Company of Hai-O Bhd - Fan, Lili (2016)
Purpose The purpose of this research is to concentrate on the business transformation of traditional Goldsmiths business and investigate particular subtle elements on how transform in the connection of Goldsmiths business measured by Balanced Scorecard Design, Methodology and Approach A qualitative method has adopted for the conduct of this research Findings The results of this research found that the effectiveness of traditional Goldsmiths business transformation can measured by the Balanced Scorecard using a before and after data comparison for all the five elements within the Balanced Scorecard. The traditional Goldsmiths business transformation is effective and the effectiveness of traditional Goldsmiths business transformation can affect by resources constraints and business owner readiness. Research Limitations and Implications The time limitations is the fundamental issue affecting this research, which limits time of data collection and scope of this research has confined in one Goldsmiths business.